Доказательство по индукции:
1 + 2 + 3 + ... + n = n(n + 1) / 2
1 + 2 + 3 + ... + n = O(n^2)
Базовый корпус:
n = 1
1 = (1 + 1) / 2
1 = 2 / 2
1 = 1
Допустим, истина до k
для k < n
:
1 + 2 + 3 + ... + k = k(k + 1) / 2
Доказательство для n = k + 1
1 + 2 + 3 + ... + k + (k + 1) = (k + 1)(k + 1 + 1) / 2
k(k + 1)/2 + (k + 1) = (k + 1)(k + 1 + 1) / 2
k(k + 1)/2 + 2(k + 1) / 2 = (k + 1)(k + 1 + 1) / 2
(k^2 + k)/2 + (2k + 2) / 2 = (k + 1)(k + 1 + 1) / 2
(k^2 + k + 2k + 2) / 2 = (k + 1)(k + 1 + 1) / 2
(k^2 + 3k + 2) / 2 = (k + 1)(k + 2) / 2
(k^2 + 3k + 2) / 2 = (k^2 + 2k + k + 2) / 2
(k^2 + 3k + 2) / 2 = (k^2 + 3k + 2) / 2
Таким образом:
1 + 2 + 3 + ... + n = n(n + 1) / 2
1 + 2 + 3 + ... + n = (n^2 + n) / 2
1 + 2 + 3 + ... + n = O(n^2)